The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.12804/revistas.urosario.edu.co/apl/a.8652
|View full text |Cite
|
Sign up to set email alerts
|

A Tríade Sombria da Personalidade: Afetos e Lócus de Controle

Abstract: A tríade sombria da personalidade —narcisismo, maquiavelismo e psicopatia— retrata características antagonistas, insensíveis e socialmente aversivas. É sabido que diversos fatores são afetados por traços de personalidade, tanto saudáveis quanto psicopatológicos. Este estudo buscou compreender a capacidade explicativa da tríade sombria nos afetos positivos e negativos e no lócus de controle. Para tanto foram realizados dois estudos. Compuseram o primeiro deles 154 participantes, com média de idade de 27,14 anos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…In a study on a sample of college students, Singh et al (2017) found a negative correlation between the two. Furthermore, a recent study by Bonfa´-Araujo et al (2020) found Machiavellianism negatively related to ELOC. Bonfa´-Araujo et al (2020), Gable et al (1990), and Solar and Bruehl (1971) also found a relationship between ILOC and Machiavellianism.…”
Section: Machiavellianismmentioning
confidence: 90%
“…In a study on a sample of college students, Singh et al (2017) found a negative correlation between the two. Furthermore, a recent study by Bonfa´-Araujo et al (2020) found Machiavellianism negatively related to ELOC. Bonfa´-Araujo et al (2020), Gable et al (1990), and Solar and Bruehl (1971) also found a relationship between ILOC and Machiavellianism.…”
Section: Machiavellianismmentioning
confidence: 90%
“…Some mixed results indicate that the composite of the Dark Triad in entrepreneur students is negatively correlated with internal control and that Machiavellianism, also in entrepreneur students, positively correlated with external control (Rapp-Ricciardi et al, 2018). In another investigation in a general community sample, psychopathy was positively correlated with internal control, and Machiavellianism negatively correlated with external control (Bonfá-Araujo et al, 2020). Concerning D, demonstrated a tendency to perceive the world as competitive and dangerous.…”
Section: Introductionmentioning
confidence: 88%
“…Narcissistic Personality Inventory-13 (NPI-13;Gentile et al, 2013). Os itens desta medida foram traduzidos por Monteiro (2017), sendo que esta versão da NPI é formada por 13 itens (ω = 0,81), tendo como objetivo mensurar o nível de narcisismo dos indivíduos. Os participantes são orientados a indicar a sua concordância (1: Discordo Fortemente; 5: Concordo Fortemente) a itens como "Eu gosto de me olhar no espelho" e "Usualmente tento me exibir quando tenho a oportunidade".…”
Section: Instrumentosunclassified